Tracer Study of Bachelor of Science in Accountancy Graduates - Sayson, Cyrill Jick O.; Asilum, Winriel G.; Pintacasi, Joleah E.; Pepania, Artchelene D.; Sumicad Jr., Eligen H. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study primarily aims to trace the employability of the Bachelor of Science in Accountancy graduates. It focuses on determining their educational background, post-graduation activities, and employment. Moreover, the study is structured to assess the importance of undergraduate programs in fostering the skills development of graduates and the applicability of the curriculum's courses to their subsequent employment. A tracer study, elucidating graduates' educational and career paths, is a vital instrument in comprehending the outcomes of academic pursuits. Employing stratified sampling techniques, strata were derived from graduates spanning the years 2018 to 2022, ensuring comprehensive representation. In scrutinizing educational backgrounds, a notable 50.6% lacked specific certifications, with the Civil Service Examination emerging as the predominant certification at 28.1%. Influential factors in course selection were diverse, with parental influence (16.0%) and the allure of immediate employment (14.5%) exerting substantial impacts. A 14.6% of respondents in the professional training category chose the designation "Bookkeeping," indicating a substantial interest in acquiring skills related to bookkeeping. The study exposed a significant 68.4% of graduates currently employed, emphasizing the consequential impact of skill mismatches on job satisfaction. Notably, 67.8% of employment remained local, indicating a balanced representation of domestic and international work opportunities. The institutional contribution to graduates' personal growth was evident, as values like environmental responsibility and service to humanity strongly influenced professional behavior. In conclusion, this tracer study, methodically executed through stratified sampling, provides nuanced insights into graduates' educational and professional trajectories, underscoring the multifaceted influences shaping their career choices and emphasizing the integral role of education in fostering ethical and successful professionals.